2009
DOI: 10.1021/ac9018846
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric Detection of 5-Hydroxytryptamine Release in the Rat Brain

Abstract: Abstract5-HT is an important molecule in the brain that is implicated in mood and emotional processes. In vivo, its dynamic release and uptake kinetics are poorly understood due to a lack of analytical techniques for its rapid measurement. Whereas fast-scan cyclic voltammetry with carbon fiber microelectrodes is used frequently to monitor sub-second dopamine release in freely-moving and anesthetized rats, the electrooxidation of 5-HT forms products that quickly polymerize and irreversibly coat the carbon elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
435
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 253 publications
(441 citation statements)
references
References 58 publications
(166 reference statements)
5
435
1
Order By: Relevance
“…11,19 Specifically, serotonin was found to increase by 380% 11 and 480%. 19 Current and previous findings in the intact brain of rats and mice are not in agreement with the data from tissue slice preparations.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…11,19 Specifically, serotonin was found to increase by 380% 11 and 480%. 19 Current and previous findings in the intact brain of rats and mice are not in agreement with the data from tissue slice preparations.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…These cyclic voltammograms identify serotonin based on the positions of the oxidation and reduction peaks. 11 We chose to study ESCIT because it is one of the most clinically useful SSRIs. 3,20 However, other SSRIs such as fluoxetine and sertraline exhibit similar modes of action (selective SERT inhibition), and we have observed similar increases in serotonin amplitude in vivo with these two agents (unpublished observations).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this scan rate, no reversal peak was observed, suggestive of an irreversible oxidation mechanism occurring at both electrodes. However other researchers have shown that at higher scan rates (>100 V s -1 ), the cathodic peak (Epc) can be observed [11,15]. 5-HT undergoes an electrochemical-chemical mechanism.…”
Section: Discussionmentioning
confidence: 90%
“…For instance, in order to fully understand these neuromodulatory effects, it will be particularly important to consider their timescale (tonic or phasic). Specifically, it will be important to obtain better insights in the degree to which commonly used 5-HT manipulations affect phasic versus tonic transmission, thus highlighting the necessity of combining temporally precise methods in freely behaving animals, such as neurophysiological recording of single 5-HT and DA neurons, electrochemical voltammetric approaches (Hashemi et al, 2009), and/or optogenetics with procedures used to study the effects of 5-HT, for example, 5,7-DHT lesions, ATD, SSRI administration, and the 5-HT transporter gene-linked polymorphism (5HTTLPR).…”
Section: Future Research Directionsmentioning
confidence: 99%